Mental Toughness And Sports Competition Anxiety Between Female Football And Hockey Players- A Comparative Study - Issac, Mathew; Raj, Sreejith; C. T., Toy; Jose, Baiju P; P, Jinsha Jayaprakash. (International Journal of Psychosocial Rehabilitation, 2025)
The purpose of the study was to compare the Sports Competition Anxiety and Mental Toughness between female Hockey and Football players. For the purpose of the study, a total of 200 national level women Hockey players and Football players were selected as the subjects. Equal number of subjects were taken from Hockey (N=100) and Football (N=100); these two categories were taken into consideration for the present study. Sports Competition Anxiety Test (SCAT) and The Psychological Performance Inventory of Mental Toughness questionnaire was used for the collection of data. The questionnaire was administrated to the athletes in study by the investigator himself. The objective of the test was explained to the athletes and they were asked to respond to each statement as truthfully as possible. As soon as they completed the test the investigator collected the response sheets. The athletes were assured of confidentiality of the answers they would give. In order to examine the hypothesis of study, descriptive statistics such as mean, standard deviation (SD), and comparative statistics such as Independent sample ‘t’ test were used. Apart from the finding it evident that there is a significant difference between the Anxiety and Mental toughness among female Hockey and Football players.